THE EFFECT OF BIRTH TYPE ON BREASTFEEDING SUCCESS AND INSOMNIA SEVERITY IN PUERPERANT WOMEN - Altıparmak, Sümeyye; Yılmaz, Ayşe Nur (Ondokuz Mayıs Üniversitesi, 2021)
Objective: This research was carried out to determine the effect of birth type on breastfeeding success and insomnia severity in puerperant women.Method: The sample of the type of cross-sectional and comparative research, between January and February 2021, to participate in research in a public hospital located in the east of Turkey has created 314 puerperal women who accepted. The data were collected using “Personal Information Form, LATCH Breastfeeding Assessment Tool and Insomnia Severity Index (ISI)”. Descriptive statistics, independent groups t test and Pearson correlation analysis were used in data analysis.Results: It was found that women who vaginally birth (n = 227) had a total score of 8.48 ± 1.47 on the LATCH Breastfeeding Assessment Tool, and an average of 10.44 ± 5.19 on the ISI. These averages were found to be 8.00 ± 2.08 and 8.78 ± 4.46, respectively, in women who had cesarean birth (n = 87). It was determined that the LATCH Breastfeeding Assessment Tool and ISI total score averages were statistically higher in women who gave birth vaginally than those who delivered by cesarean section (p <0.05). In addition, it was observed that as the insomnia severity increased in women who had vaginal birth, breastfeeding success decreased significantly (p <0.05), while there was no statistical relationship between insomnia severity and breastfeeding success in women who gave birth by cesarean section (p ?0.05).Conclusion and Suggestions: In this study, it was determined that breastfeeding success and insomnia severity in women who gave vaginal birth were higher than women who gave birth by cesarean section.

Amaç: Bu araştırma, doğum şeklinin emzirme başarısı ve annelerdeki uykusuzluk şiddetine etkisini belirlemek amacıyla yapıldı.Yöntem: Kesitsel ve karşılaştırmalı tipte olan araştırmanın örneklemini, Ocak – Şubat 2021 tarihleri arasında, Türkiye’nin doğusunda bulunan bir kamu hastanesinde yatan 314 lohusa oluşturdu. Veriler, “Kişisel Tanıtım Formu, LATCH Emzirme Tanılama Ölçüm Aracı ve Uykusuzluk Şiddeti İndeksi (UŞİ)” ile toplandı. Verilerin analizinde tanımlayıcı istatistikler, bağımsız gruplarda t testi ve pearson korelasyon analizi kullanıldı.Bulgular: Normal doğum yapan kadınların (n=227) LATCH Emzirme Tanılama Ölçeği toplam puan ortalamasının 8.48±1.47, UŞİ toplam puan ortalamasının 10.44±5.19 olduğu ve bu ortalamaların Sezaryen Doğum yapan kadınlarda (n=87) sırasıyla; 8.00±2.08 ve 8.78±4.46 olduğu saptanmıştır. LATCH Emzirme Tanılama Ölçeği ve UŞİ toplam puan ortalamalarının normal doğum yapan kadınlarda sezaryenle doğum yapanlara oranla istatistiksel açıdan daha yüksek olduğu belirlenmiştir (p<0.05). Ayrıca, normal doğum yapan kadınlarda uykusuzluk şiddeti arttıkça emzirme başarısının anlamlı düzeyde azaldığı görülürken (p<0.05), sezaryenle doğum yapan kadınlardaki uykusuzluk şiddeti ve emzirme başarısı arasında herhangi bir istatistiksel ilişki saptanmamıştır (p ?0.05). Sonuçlar ve Öneriler: Bu araştırmada normal doğum yapan kadınlardaki emzirme başarısı ve uykusuzluk şiddetlerinin sezaryenle doğum yapan kadınlara oranla daha yüksek olduğu belirlenmiştir.
Doğum Şeklinin Emzirme Başarısı ve Annelerdeki Uykusuzluk Şiddetine Etkisi
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi